Respuesta :
Simplifying
2p + -12 = 12 + -2p
Reorder the terms:
-12 + 2p = 12 + -2p
Solving
-12 + 2p = 12 + -2p
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '2p' to each side of the equation.
-12 + 2p + 2p = 12 + -2p + 2p
Combine like terms: 2p + 2p = 4p
-12 + 4p = 12 + -2p + 2p
Combine like terms: -2p + 2p = 0
-12 + 4p = 12 + 0
-12 + 4p = 12
Add '12' to each side of the equation.
-12 + 12 + 4p = 12 + 12
Combine like terms: -12 + 12 = 0
0 + 4p = 12 + 12
4p = 12 + 12
Combine like terms: 12 + 12 = 24
4p = 24
Divide each side by '4'.
p = 6
Simplifying
p = 6
Simplifying 2p + -12 = 12 + -2p Reorder the terms: -12 + 2p = 12 + -2p Solving -12 + 2p = 12 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. -12 + 2p + 2p = 12 + -2p + 2p Combine like terms: 2p + 2p = 4p -12 + 4p = 12 + -2p + 2p Combine like terms: -2p + 2p = 0 -12 + 4p = 12 + 0 -12 + 4p = 12 Add '12' to each side of the equation. -12 + 12 + 4p = 12 + 12 Combine like terms: -12 + 12 = 0 0 + 4p = 12 + 12 4p = 12 + 12 Combine like terms: 12 + 12 = 24 4p = 24 Divide each side by '4'. p = 6 Simplifying p = 6